Research on Long-term Different Fertilization Types on Microbial Diversity with AOB gene in Tobacco Field Soil - Yuzhou Jiang, Shunhui Chen, Wenqing Li, Qingli Liu, Zhihong Li, Yungui Zhang, Yan Zhang, Peng Wang, Jiaxin Li (Forest Chemicals Review)
The objective of this study were analyzed that Long-term fertilization affected the AOB gene structure and abundance of soil bacteria in flue-cured tobacco field. There are three treatments in this study, respectively T1 for Chemical fertilizer, T2 for chemical fertilizer + straw returning and T3 for chemical fertilizer + straw returning + cake fertilizer. This study studied the effects of inorganic nitrogen and bacterial diversity in tobacco rhizosphere soil. The results showed that the relative abundance of Proteobacteria was the highest in the bacterial community, ranging from 58.68% to 69.00%, which was positively correlated with nitrate nitrogen and negatively correlated with ammonium nitrogen. The LEf Se evolutionary cladistic diagram of soil microorganisms showed that the bacterial population appeared in tobacco field treated with straw or cake fertilizer. In conclusion, long-term straw returning combined with cake fertilizer can increase inorganic nitrogen content and improve the microbial diversity with AOB gene in tobacco field.